Risk factors and lethality of laboratory-confirmed bloodstream infection caused by non-skin contaminant pathogens in neonates - Roberta M.C. Romanelli; Lêni M. Anchieta; Maria Vitoria A. Mourão; Flávia A. Campos; Flavia C. Loyola; Paulo Henrique O. Mourão; Guilherme A. Armond; Wanessa T. Clemente; Maria Cândida F. Bouzada (Brazilian Society of Pediatrics, 2013)
Objective: To evaluate risk factors and lethality of late onset laboratory-confirmed bloodstream infection (ICSLC) in a Brazilian neonatal unit for progressive care (NUPC). Methods: This was a case-control study, performed from 2008 to 2012. Cases were defined as all newborns with late onset ICSLC, excluding patients with isolated common skin contaminants. Controls were newborns who showed no evidence of late onset ICSLC, matched by weight and time of permanence in the NUPC. Variables were obtained in the Hospital Infection Control Committee (HICC) database. Analysis was performed using the Statistical Package for the Social Sciences (SPSS). The chi-squared test was used, and statistical significance was defined as p < 0.05, followed by multivariate analysis. Results: 50 patients with late onset ICSLC were matched with 100 patients without late onset ICSLC. In the group of patients with late onset ICSLC, a a significant higher proportion of patients who underwent surgical procedures (p = 0.001) and who used central venous catheter (CVC) (p = 0.012) and mechanical ventilation (p = 0.001) was identified. In multivariate analysis, previous surgery and the use of CVC remained significantly associated with infection (p = 0.006 and p = 0.047; OR: 4.47 and 8.99, respectively). Enterobacteriacea was identified in 14 cases, with three (21.4%) deaths, and Staphylococcus aureus was identified in 20 cases, with three (15%) deaths. Conclusions: Surgical procedures and CVC usage were significant risk factors for ICSLC. Therefore, prevention practices for safe surgery and CVC insertion and manipulation are essential to reduce these infections, in addition to training and continuing education to surgical and assistance teams.